2017
DOI: 10.1093/ntr/ntx011
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Youth and Young Adult Perspectives on a Culturally Tailored Group Smoking Cessation Program

Abstract: IntroductionThe prevalence of smoking among LGBTQ youth and young adults (YYAs) is much higher than that of non-LGBTQ young people. The current study explored LGBTQ YYA perceptions of a culturally tailored group smoking cessation counselling program, along with how the intervention could be improved.MethodsWe conducted focus groups (n = 24) with 204 LGBTQ YYAs in Toronto and Ottawa, Canada. Open-ended questions focused on their feelings, likes and dislikes, concerns and additional ideas for a culturally tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The 20 articles included in this scoping review reported on 15 intervention programs, including a smoking cessation intervention for 'LGBT' smokers reported in two articles (Matthews, Breen, et al, 2019;Matthews, Steffen, et al, 2019), and a smoking cessation intervention for young LGBTQ people reported in three articles (Ramo et al, 2019;. Three of the articles described a single study that evaluated the acceptability of three hypothetical interventions, rather than delivery of actual interventions (Baskerville et al, 2016(Baskerville et al, , 2017(Baskerville et al, , 2018. We have organised the types of intervention described across this review into three categories: therapeutic (interventions based in clinic settings or involving therapeutic modalities; n = 9), online (interventions delivered via digital platforms and technologies; n = 7) and scene-based (interventions that took place at the material sites in which LGBTQ communities interact socially; n = 3).…”
Section: Re Sultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 20 articles included in this scoping review reported on 15 intervention programs, including a smoking cessation intervention for 'LGBT' smokers reported in two articles (Matthews, Breen, et al, 2019;Matthews, Steffen, et al, 2019), and a smoking cessation intervention for young LGBTQ people reported in three articles (Ramo et al, 2019;. Three of the articles described a single study that evaluated the acceptability of three hypothetical interventions, rather than delivery of actual interventions (Baskerville et al, 2016(Baskerville et al, , 2017(Baskerville et al, , 2018. We have organised the types of intervention described across this review into three categories: therapeutic (interventions based in clinic settings or involving therapeutic modalities; n = 9), online (interventions delivered via digital platforms and technologies; n = 7) and scene-based (interventions that took place at the material sites in which LGBTQ communities interact socially; n = 3).…”
Section: Re Sultsmentioning
confidence: 99%
“…LGBTQ people who were already engaged with existing clinical or support programs (van den Berg et al, 2014;Grady et al, 2014). In terms of who was targeted, half of the articles (n = 10) were inclusive of both sexuality and gender diversity by recruiting 'LGBT' (Fallin et al, 2015;Matthews, Breen, et al, 2019;Matthews, Steffen, et al, 2019), 'LBGTQ' or 'LGBTQ+' (Baskerville et al, 2017(Baskerville et al, , 2018Ramo et al, 2019) or 'sexual and gender minority' participants (Grady et al, 2014;Vogel, Belohlavek, et al, 2019;Vogel, Thrul, et al, 2019). The remaining half of the articles (n = 10) targeted specific subpopulations: young gay and bisexual men (GBM) (Thompson et al, 2015), who were HIV negative or of unknown HIV status (van…”
Section: What Does the Targeting Of Interventions Tomentioning
confidence: 99%
See 3 more Smart Citations